2019
DOI: 10.1016/j.cub.2019.07.087
|View full text |Cite
|
Sign up to set email alerts
|

Galanin Neurons Unite Sleep Homeostasis and α2-Adrenergic Sedation

Abstract: Highlights d This is the first identification of a cell type underlying sleep homeostasis d Preoptic galanin neurons are essential for sleep homeostasis d Galanin neurons mediate the sedative and hypothermic actions of dexmedetomidine d Dexmedetomidine causes an EEG delta power rebound dependent on galanin neurons

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
88
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(90 citation statements)
references
References 63 publications
(92 reference statements)
2
88
0
Order By: Relevance
“…Consistent with the shared circuits hypothesis, previous work using cFos-dependent tagging and selective stimulation of previously active (tagged) neurons showed that sedation with dexmedetomidine and NREM sleep are produced, in part, by the same neuronal array within the preoptic area [17]. Preoptic galanin neurons mediate, in part, sleep homeostasis as well as the sedative and hypothermic effect of dexmedetomidine [18]. However, dexmedetomidine is clinically used in humans as a sedative, and its hypnotic, NREM-sleep-like effect is readily reversible upon stimulation, unlike general anesthesia with isoflurane, a halogenated ether used at clinically relevant concentrations in the current study.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Consistent with the shared circuits hypothesis, previous work using cFos-dependent tagging and selective stimulation of previously active (tagged) neurons showed that sedation with dexmedetomidine and NREM sleep are produced, in part, by the same neuronal array within the preoptic area [17]. Preoptic galanin neurons mediate, in part, sleep homeostasis as well as the sedative and hypothermic effect of dexmedetomidine [18]. However, dexmedetomidine is clinically used in humans as a sedative, and its hypnotic, NREM-sleep-like effect is readily reversible upon stimulation, unlike general anesthesia with isoflurane, a halogenated ether used at clinically relevant concentrations in the current study.…”
Section: Discussionsupporting
confidence: 62%
“…These studies, in conjunction with our complementary findings, should prompt the field to consider exploring additional brain regions and nuclei beyond those classically known to regulate sleep and wakefulness. Furthermore, it is becoming increasingly evident that widespread neural networks encompassing multiple nuclei within the rostral hypothalamus orchestrate the features of complex behaviors and states, such as sleep, sedation, and anesthesia [10,11,17,18,26,27]. An unexpected finding was that activation of glutamatergic neurons in the MnPO reduced REM sleep and did not alter NREM sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Although the delta (0.5 to 4 Hz) oscillations that occur in the NREM sleep EEG probably arise from a neocortex-thalamus dialogue 18 , circuits that drive the actual initiation of sleep are usually regarded as "bottom-up": hypothalamic, midbrain and brainstem aminergic, glutamatergic and GABAergic neurons control the onset of sleep-wake states [18][19][20][21][22][23][24][25][26][27] . In general, behavioral responses to drives such as hunger and thirst are integrated in the hypothalamus, which then influences the neocortex and other brain regions to reinforce the required homeostatic response at a behavioral level 28,29 .…”
mentioning
confidence: 99%
“…Surprisingly, animals showed largely normal wake behavior when stimulated during sedation, even though their peripheral body temperature was reduced to values close to room temperature. Furthermore, our finding that continuous intense stimulation of the LPO can produce sustained wakefulness and hypothermia at the same time, further highlights that our understanding of the circuitry involved in vigilance states control and thermoregulation is incomplete (Kroeger et al, 2018;Ma et al, 2019;Zhao et al, 2017).…”
Section: Discussionmentioning
confidence: 94%
“…This model was able to account for rapid and complete transitions between sleep and wakefulness, and for preventing state instability (Mochizuki et al, 2004) or an occurrence of mixed, hybrid states of vigilance (Mahowald et al, 2011). However, over the last decade, our knowledge of subcortical brain nuclei that control sleep has expanded steadily, leading to the identification of functional specialization within the sleep-control network, and in parallel, highlighting a previously underappreciated complexity (Chung et al, 2017;Herrera et al, 2016;Kroeger et al, 2018;Liu and Dan, 2019;Liu et al, 2020;Ma et al, 2019;Oishi et al, 2017;Weber et al, 2018;Zhang et al, 2015;Zhong et al, 2019).…”
Section: Introductionmentioning
confidence: 99%